Applying the Digital Curation Lessons Learned from American Memory - Liz Madden (International Journal of Digital Curation, 2008)
American Memory, launched in 1995, was the Library of Congress’s debut web presentation and the primary product of the National Digital Library Program. More than 700,000 described digital items in 90 collections were added to American Memory in those first five years, including content from 23 external organizations. These materials were digitized, assembled and presented without tools designed specifically for the work and before the development of approved standards for the creation, presentation, or exchange of digital content. Valuable lessons about all levels of digital curation emerged from this early foray into digital library work, and many of the issues have persisted into current digital library efforts at the Library. This article focuses primarily on lessons learned about the conceptualization, creation, receipt, and preservation actions for digital content. It describes how strategies developed early on to manage the diverse and heterogeneous digital content helped inform later practices and were applied to legacy data in an effort to ensure their sustainability, flexibility and shareability into the future.